Simulation and Modeling of Convective Mixing of Carbon Dioxide in Geological Formations - Marco De Paoli; Francesco Zonta; Lea Enzenberger; Eliza Coliban; Sergio Pirozzoli (Geophysical Research Letters)
Abstract We perform large‐scale numerical simulations of convection in 3D porous media at Rayleigh‐Darcy numbers up to Ra=8×104. To investigate the convective mixing of carbon dioxide (CO2) in geological formations, we consider a semi‐infinite domain, where the CO2 concentration is constant at the top and no flux is prescribed at bottom. Convection begins with a diffusion‐dominated phase, transitions to convection‐driven solute finger growth, and ends with a shutdown stage as fingers reach the bottom boundary and the concentration in the system increases. For Ra≥5×103, we observe a constant‐flux regime with dissolution flux stabilizing at 0.019, approximately 13% higher than in 2D estimates. Finally, we provide a simple and yet accurate physical model describing the mass of solute entering the system throughout the whole mixing process. These findings extend solutal convection insights to 3D and high‐Ra, improving the reliability of tools predicting the long‐term CO2 dynamics in the subsurface.